Advantages of Small Incision Lenticule Extraction (SMILE) for Mass Eye and Ear Special Issue. (18th May 2020) - Ahmed, Amani A.; Hatch, Kathryn M.
ABSTRACT: This review summarizes the advantages of Small-incision lenticule extraction (SMILE), including improved patient intraoperative experience, improved postoperative ocular surface, low incidence of regression, low re-treatment rates, and advantageous biomechanical corneal stability. Visual and refractive outcomes are similar to those achieved with LASIK, notably in large population studies. Since the inception of SMILE almost 10 years ago, the procedure has been rapidly growing in popularity. With the implementation of the novel SMILE technology in their practice, refractive surgeons generate excitement and potential for expanding the refractive market. Other parts of the world, including Asia, Europe, and Russia, SMILE has become the most popular refractive procedure performed. It is speculated that as SMILE continues to grow in popularity in the US since FDA approval in 2016 and more refractive surgeons implement this technology into their practice, it will drive an increase in the refractive market similar to what is seen in other countries.